Pengembangan Media Pembelajaran Kartu Domino Ekonomi - Muhammad Ilyas Thamrin Tahir; Nur Arisah; Dewi Sakinah Rahmadani; Mustari Mustari; A. Sri Astika Wahyuni (Program Studi Sarjana Terapan PTM FT UNM, 2024)
The partners of this Community Partnership Program (PKM) are the Principal, Teachers, and Staff of SMAN 6 Barru. The priority problem underlying this training activity is to improve the effectiveness of the learning process by applying domino card learning media, because the use of effective and interactive learning media can increase students' interest and motivation to learn. The methods used were lectures, demonstrations, discussions, questions and answers, and accompanying partners. The results achieved are (1) Partners have knowledge related to domino card learning media, (2) Partners can apply domino card learning media (3) Partners have the ability to develop interactive learning media.